2016
DOI: 10.1002/oby.21623
|View full text |Cite
|
Sign up to set email alerts
|

OSA screening with the pediatric sleep questionnaire for adolescents undergoing bariatric surgery in teen‐LABS

Abstract: Objective Obstructive sleep apnea (OSA) is reported in 70% of adolescents who present for bariatric surgery. The Pediatric Sleep Questionnaire (PSQ) was developed to identify children at risk for OSA, but is not validated in adolescents with obesity. The aims of this study:1)to assess validity of the PSQ to detect OSA, and 2)determine the correlation between anthropometric and polysomnography measurements. Methods Cross-sectional assessment of Teen-Longitudinal Assessment of Bariatric Surgery (Teen-LABS) par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 15 publications
(22 reference statements)
2
7
0
Order By: Relevance
“…The PSQ demonstrated poor sensitivity and specificity at varying AHI cut-offs in our snoring population. These findings are consistent with earlier failed attempts at utilizing the PSQ as an OSA screening tool for other high-risk populations, including craniofacial disorder and obesity 21,22 .…”
Section: Conflict Of Interest Statementsupporting
confidence: 90%
“…The PSQ demonstrated poor sensitivity and specificity at varying AHI cut-offs in our snoring population. These findings are consistent with earlier failed attempts at utilizing the PSQ as an OSA screening tool for other high-risk populations, including craniofacial disorder and obesity 21,22 .…”
Section: Conflict Of Interest Statementsupporting
confidence: 90%
“…Similarly, our study found physician assessment for snoring in children with SCA, at each health maintenance visit, to be a sensitive albeit non-specific screening measure. In the snoring population, poor sensitivity and specificity at varying AHI cut-offs is consistent with earlier failed attempts at utilizing the PSQ as an OSA screening tool for high-risk populations, including craniofacial disorder and obesity 22,23…”
Section: Discussionsupporting
confidence: 75%
“…In the snoring population, poor sensitivity and specificity at varying AHI cut-offs is consistent with earlier failed attempts at utilizing the PSQ as an OSA screening tool for high-risk populations, including craniofacial disorder and obesity. 22,23 Limitations in this real-world study include a PSG completion rate of 60.8% for the snoring group, possibly involving those with greater concerns about sleep-disordered breathing, which also compares to 66% PSG completion rate in the Sleep and Asthma Cohort. Referring a patient for a PSG involves time, education, and cost which are factors that may have negatively impacted our cohort (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…The severity seems to increase with age, and children with OSA experience increased morbidity and mortality independent of other risk factors [5860]. The prevalence of OSA is even greater among adolescents presenting for MBS, ranging from 46% to 70% [32,60,61]. Recent data demonstrate substantial improvement and/or resolution after MBS in adolescents, consistent with the outcomes in adults, with no increased morbidity or mortality [62,63].…”
Section: Obesity Disease-related Co-morbidities and Outcomesmentioning
confidence: 85%